Research on Energy Consumption of Building Layout and Envelope for Rural Housing in the Cold Region of China. (February 2019) - Cheng, T.; Wang, N.; Liu, C.H.
Abstract: Rural housing is an important part of residential buildings in China, which has large construction amount, high energy consumption and large potential for energy saving. Unreasonable building layout and poor thermal performance of building envelope are the main reasons for high energy consumption through field survey of rural housing in cold region. Based on computer-aided simulation, this study uses DesignBuilder to simulate the energy consumption of typical rural housing, and compares it with other energy consumption under different strategies of building layout and envelope. Energy-saving strategies of building layout and envelope suited for rural housing are obtained. The research has significant reference value to the energy-saving design of rural housing.